Analisis Terhadap Produk Cacat Tersembunyi Ditinjau dari Undang-Undang Perlindungan Konsumen - hadis, hadis; benni rusli (DOKTRINA: JOURNAL OF LAW, 2024)
The purpose of this research is to find out the provisions for hidden defective products in four-wheeled vehicles in terms of the Consumer Protection Law and to find out the judge's considerations in decision Number 193/PDT/G/2019/PN.Jkt.Utr. The method used in this research is a normative juridical method with a conceptual approach and statutory regulations. The legal materials used are materials consisting of primary, secondary and tertiary legal materials. The results of the research are that the position of the seller as a business owner as stipulated in the consumer protection law is to provide as detailed information as possible and the consumer is obliged to read and understand this information so that there will be no disinformation and then in the judge's consideration there will be defects in formulating arguments so that in this case it is detrimental to the seller as the defendant has carried out his duties in accordance with statutory regulations.